Conserving Local Water Springs (Mata Air) Through Community-Based Natural Resource ManagementIn Highland Bali - Elena Kitanovska; Nikola Markovski; Marija Georgieva (Yayasan Adra Karima Hubbi, 2026)
Water springs (mata air) in the highland regions of Bali play a vital role in sustaining local livelihoods, cultural identity, and ecological balance. Increasing pressures from tourism expansion, agricultural intensification, and changes in land use have led to declining water quality and reduced discharge, threatening both environmental sustainability and community well-being. Community-Based Natural Resource Management (CBNRM) has emerged as a promising approach to safeguard local water resources by integrating traditional ecological knowledge, collective stewardship, and participatory governance. This study aims to examine how community-driven water spring conservation initiatives contribute to sustainable resource management and socio-environmental resilience in highland Bali. A mixed-methods research design was employed, combining quantitative assessments of water quality and discharge stability with qualitative analysis of local governance practices. Data were collected through water sampling, structured observations, household surveys, and in-depth interviews with customary leaders, farmers, and conservation volunteers. Quantitative data were analyzed using descriptive comparison to identify ecological changes, while qualitative data underwent thematic coding to assess community engagement, values, and institutional support. The findings indicate that community-based conservation improved spring conditions through reforestation efforts, traditional zoning enforcement, and adoption of environmentally responsible agricultural practices. Participants demonstrated stronger awareness of water ecosystem functions and shared responsibility for long-term sustainability. The reactivation of customary regulations (awig-awig) and ritual practices strengthened compliance and collective monitoring efforts, enhancing institutional legitimacy. This study concludes that integrating cultural traditions with participatory ecological management produces effective, locally grounded conservation outcomes. Strengthening CBNRM strategies in highland Bali can support broader water security goals, climate resilience, and intergenerational environmental heritage protection. Policy alignment and multi-stakeholder collaboration will be essential to maintain ecological gains and scale the model to other sensitive watershed regions.